Factors associated with sexually transmitted infections among reproductive age women in Ivory Coast: evidenced by 2021 Ivory Coast Demographic and Health Survey - Mankelkl, Gosa; Kinfe, Beletu (Frontiers in Global Women's Health, 2025)
BackgroundGlobally, sexually transmitted infections (STIs) continue to be a major public health problem. STIs are a major cause of morbidity and mortality in many developing countries due to their effects on reproductive and child health and their role in spreading HIV infection. This study ' to determine the factors associated with STIs among women in Ivory Coast using data from the 2021 Ivory Coast Demographic and Health Survey (DHS).MethodsA total of 14,877 women from the 2021 Ivory Coast Demographic and Health Survey participated in this study. The Ivory Coast DHS employed a community-based cross-sectional study design for data collection. STATA version 14 was used for data extraction, recoding, descriptive analysis, and analytical analysis. Bivariable analysis was performed to identify factors for multivariable analysis. In the multivariable analysis, factors with a significance level of P < 0.05 were considered significant predictors of STIs among reproductive-age women. Finally, frequency, percentage, and odds ratios with a 95% confidence interval were reported.ResultThis study includes a total weighted sample of 14,877 women from the 2021 Ivory Coast Demographic and Health Survey. The prevalence of STIs among reproductive-age women in the last 12 months was 6.82%, with a 95% CI (6.42, 7.23). The results of the multivariate analysis showed that among women, STIs were statistically and significantly associated with age range of 20–24 years [adjusted odds ratio (AOR): 1.558, 95% CI: (1.108, 2.359); P = 0.011], 25–29 years [AOR: 1.523, 95% CI: (1.089, 2.129); P = 0.014], and 30–34 years [AOR: 1.655, 95% CI: (1.191, 2.300); P = 0.003]; living in Denguele [AOR:2.138, 95% CI: (1.328, 3.439); P = 0.002], Montagnes [AOR: 2.930, 95% CI: (1.909, 4.497); P = 0.0001], and Zanzan [AOR: 2.330, 95% CI: (1.476, 3.679); P = 0.0001]; being married [AOR: 0.705, 95% CI: (0.520, 0.975); P = 0.034]; being Muslim [AOR: 0.785, 95% CI: (0.621, 0.993); P = 0.011]; listening to radio at least once a week [AOR: 1.524, 95% CI: (1.241, 1.871); P = 0.0001]; watching television less than once a week [AOR: 1.649, 95% CI: (1.156, 2.352); P = 0.006]; using the internet almost every day [AOR: 1.359, 95% CI: (1.081, 1.708); P = 0.008]; having a history of a terminated pregnancy [AOR: 1.170, 95% CI: (1.017, 1.376); P = 0.043]; using modern contraceptives [AOR: 1.213, 95% CI: (1.032,1.427); P = 0.0001]; and being tested for HIV [AOR: 1.342, 95% CI: (1.149, 1.569); P = 0.0001].Conclusion and recommendationsThis study found that nearly seven out of a hundred reproductive-age women in Ivory Coast had sexually transmitted infections, influenced by factors such as age group, region, religion, marital status, media exposure (reading magazines, watching television, and using the internet), history of a terminated pregnancy, and contraceptive utilization. Therefore, healthcare providers and policymakers should focus on these specific predictors to reduce STIs among reproductive-age women.